Deconstructing the Concept of Corporate Social Responsibility: Social Investment on Luwu Indigeous Society - Rahmawati Rahmawati (Universitas Muhammadiyah Yogyakarta, Indonesia, 2018)
This research deconstructed the values contained in the concept of Corporate Social Responsibility (CSR) which is used by company for social investment aimed at prospering the community. In fact, consideration on such investment is merely for the profit and reputation of the company. The logos in this research is capitalist which is still the ideology of CSR so that deconstruction is conducted using symbol value of Kedatuan Luwu (Pakka and Payung Ri Luwu). The reality of corporate social responsibility is still on the implementation of handling negative impact caused by company activity. The company operates still with the purpose of maximizing profit which is still filled with material factors based on capitalist ideology. The deconstructed value is the value of profit that is taken into consideration is material in social activities that lead to the concept of capitalism. The intended profit should be the profit that becomes the economic impact of the activity so that the company earns profit and reputation done with dignity before the community and God. The methodology used was qualitative with the paradigm of postmodernism by deconstructing the indigenous symbols of Kedatuan Luwu by including